South African environmental reporting : a test of the legitimacy theory. - Loate, Boitumelo (My University, 2014)
This study examines the corporate environmental disclosures of South African mining organisations from 2009 to 2011 to establish the level and type of these environmental disclosures. An examination is made of mining organisations’ media articles to establish whether their environmental disclosures can be explained by the concept of an implicit social contract. Legitimacy theory posits that an organisation needs to be aware of all their stakeholders’ needs and needs to portray themselves as acting in line with stakeholder values and norms to ensure their continued success. Although environmental reporting has been on the strategic agenda of several organisations disclosures in South Africa, only a minority of research papers have explored how an environmental crisis may impact upon the provision of such disclosures. This paper will help fill this void by performing an examination of management communication strategies, organisational actions and the change in the level of environmental disclosures contained in the mining organisations’ annual report as a result of the acid mine drainage incident that occurred in late 2009. Media articles during and after the mining organisations’ legitimacy had been challenged were examined using Suchman’s (1995) three types of legitimacy: pragmatic, cognitive and moral to identify the type of legitimacy used in the context of a developing country. Regarding the annual report disclosures and media articles’ communication strategies, results were found to be consistent with the legitimacy theory. They indicate that South African mining organisations use mostly the repair strategy in attempting to change the perceptions of the public after an environmental crisis. The strategies utilised by the mining industry in the media disclosures are expected of an organisation in crisis. The mining industry used, primarily, repair strategies in interacting with its relevant stakeholders. The study’s finding that maintenance strategies were the least of the three types of legitimacies is consistent with an industry in crisis. Even though the mining industry primarily used the repair legitimisation tactic, the range of legitimacy techniques has proved to be a finding worth discussing. The mining industry did not completely avoid the event i.e. use disclaimer strategies. Overall, the mining organisations reacted to the heighted institutional pressures by increasing their environmental disclosures and disclosed environmental information that conformed to stakeholders’ values and persuaded society to view acid mine drainage as less problematic than it was reported to be.
Keywords: Social contract; Environmental disclosures; Organisational legitimacy